A festa rítmica de Paulo Paulelli: padrões rítmicos, polirritmias e modulações métricas nas conduções do contrabaixista - Eduardo Brasil Pereira Santana (2023)
In this work, it is understood that it is important to understand how the bass line (electric and acoustic) is developed in samba conductions in the context of instrumental music. Since the bass is a basic instrument in several formations, its lines can present different approaches within a given musical genre. In view of this, we decided to analyze rhythmic aspects of the lines of bassist Paulo Paulelli, a prominent instrumentalist on the national scene, with contemporary production extremely relevant to the theme. Two recordings of the bass player with the Trio Corrente group were selected. We defined some parameters for the selection of songs to be analyzed, which led to the choice of Maracangalha (2016), a samba with alternating beats, as well as Amor até o fim (2019), which presents different manipulations of the sensation of time. With the aim of compiling, mapping and analyzing the set of rhythmic elements used by Paulelli, we transcribe and point out some recurring patterns in the bassist's lines. As a way of substantiating the work, we relied on authors such as Hoenig & Weidenmueller (2009, 2012), Carvalho (2006), Syllos & Montanhaur (2003), Souza (2007) and Giffoni (1997). Thus, our methodology was based on transcribing the bass line note by note, making use of the instruments that helped us during this process. We highlight the use of software like Transcribe! and Finale, as well as a notebook, an audio interface, high-fidelity headphones and an electric bass. With the analyzes of the transcriptions, it was possible to identify rhythmic patterns frequently used in samba conductions, particular patterns of the bass player, as well as polyrhythmic elements, some like metric modulations, core rhythm and core groove.